International trade finance - Watson, Alasdair; Cowdell, Paul; Hyde, Derek; Watson, Alasdair (Canterbury : The Institute of Bankers, 2003)
Provides a sound understanding of international trade finance including the foreign exchange and support services provided for exporters, importers and merchants.
Includes index.
lje 12/12/18
Loans
Keywords: International finance; Finance; Commerce; International trade